2021
DOI: 10.1042/bsr20210337
|View full text |Cite
|
Sign up to set email alerts
|

Genetic characteristics and prognostic implications of m1A regulators in pancreatic cancer

Abstract: Studies have identified the methylation of N1 adenosine (m1A), an RNA modification, playing an important role in the progression of the tumorigenesis. This study aimed to analyze the genetic characteristics and prognostic value of m1A regulators in pancreatic cancer. In this study, data on gene mutations, single-nucleotide variants (SNVs), and copy number variation (CNV) were obtained from 363 patients with pancreatic cancer in the Cancer Genome Atlas (TCGA) database, and survival analysis was performed using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 43 publications
1
41
0
Order By: Relevance
“…Recent studies have revealed that the alteration of m1A regulators is closely associated with multiple tumors including hepatocarcinoma, colon cancer, pancreatic cancer, cervical cancer, and glioma. Shi et al (2020) , Zheng et al (2021) found that the expression of m1A regulators has great prognostic value in hepatocarcinoma and pancreatic cancer ( Shi et al, 2020 ; Zheng et al, 2021 ). Gao et al (2021) indicated that m1A regulator–mediated modification patterns play a crucial role in tumor microenvironment–infiltrating immune cells and the prognosis of colon cancer ( Gao et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have revealed that the alteration of m1A regulators is closely associated with multiple tumors including hepatocarcinoma, colon cancer, pancreatic cancer, cervical cancer, and glioma. Shi et al (2020) , Zheng et al (2021) found that the expression of m1A regulators has great prognostic value in hepatocarcinoma and pancreatic cancer ( Shi et al, 2020 ; Zheng et al, 2021 ). Gao et al (2021) indicated that m1A regulator–mediated modification patterns play a crucial role in tumor microenvironment–infiltrating immune cells and the prognosis of colon cancer ( Gao et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…14 The expression of m 5 C regulators is also linked to a variety of human cancers, 15,16 and m 1 A is considered important in the regulation of tumor development. [17][18][19] This study was designed to investigate the role of m 5 C and m 1 A regulators in CRC prognosis (using bioinformatics methods) and to analyze the association between these regulators and differences in survival as well as the clinicopathological characteristics and TIM in CRC tissues. Furthermore, this study helps to explore novel biomarkers that predict the therapeutic efficacy of current treatments and benefit therapeutic modulation.…”
Section: Introductionmentioning
confidence: 99%
“…In pancreatic cancer, m1A regulator genetic variations are related to clinical stage, and CNVs are closely associated with the expression of m1A regulators. Notably, the expression level of ALKBH1 is closely associated with the prognosis of patients with pancreatic cancer ( 22 ). Li et al.…”
Section: Discussionmentioning
confidence: 99%